Analisa Perancangan Penyediaan Mesin Industri Rumah Tangga Pada PT. Innovation Household Of Life - Lisma Yeni Pandia; Yudi Yudi (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2022)
home industry engine provision will be home industry machines provision that be marketed and machines can also be provided to pass an order that ordered by a customer. with home industry engine provision existence has aimed so that insides household can have income with machines that bought from innovation household of life. but in system arrangement or performance that built for stock information system often bot regular so that result that created becoming not perfect, so that wanted good analysis by using Context Diagram and also DFD in will build a stock system later will produce output better again.Keywords: Innovation Household Of Life, Home Industry, Machinery, Design, DFD